The Sounds of Picturebooks for English Language Learning - M. Teresa Fleta Guillén (CLELEjournal, 2017)
Picturebooks have long been recognised to aid language development in both first and second language acquisition. This paper investigates the relevance of the acoustic elements of picturebooks to raise phonological awareness and to fine-tune listening. In order to enhance the learners' aural and oral skills for English language development, the paper proposes that listening to stories from picturebooks plays a most important role for raising awareness of the sound system of English in child second-language learners. To provide practical advice for teachers of young learners, this article describes the ways that picturebooks promote listening and speaking and develops criteria to select picturebooks for English instruction focusing on the acoustic elements of language.